Shared Entertainment, Shared Opinions: The Influence of Social TV Comments on the Evaluation of Talent Shows. Issue 1 (2nd January 2018) - Winter, Stephan; Krämer, Nicole C.; Benninghoff, Brenda; Gallus, Christine
Abstract : The present research investigated whether co-viewer comments in social TV interactions are able to enhance or weaken media effects. With the example of talent shows, the valence of co-viewer comments (pro/contra/none) as well as the type of content (antisocial behavior vs. conventional performance) were varied in an experiment (N = 117). Results showed that participants' own comments and their private attitudes about the judges varied in line with comment valence. Findings suggest that social TV viewers are prone to social influence of their co-viewers, which might amplify problems regarding the portrayal of antisocial behavior in reality TV.